Des nourrissons en danger : les représentations de la relation mère-enfant dans la revue suisse Pro Juventute des années 1920 aux années 1970 - Bettina Grubenmann; Michel Christian (Genre & Histoire)
The mother-child relationship was one of the central issues dealt with in the journal Pro Juventute that was edited by the Pro Juventute foundation, a major player in the field of public health and child welfare in Switzerland in the 20th century. In addressing the mother-child issue, Pro Juventute showed great stability, drawing on the breastfeeding mother as a social model. As breastfeeding declined and infant mortality dropped from the 1930s on, the discourse moved to the issue of the infant’s psychological well-being, as new reasons were found to justify the exclusivity of the mother-child relationship, with the fathers coming into the picture only in the 1970s. On the other hand, the journal made the effort to take into account other realities contradicting its own norms such as mothers’ paid work and child-care in day nurseries and infant homes. By doing so, it valued women’s professionalization only in the field of early childhood. This stance had a real emancipatory potential at the beginning of the 20th century, which however had faded away by the 1970s.